MERESPON NALAR KEBIJAKAN NEGARA DALAM MENANGANI PANDEMI COVID 19 DI INDONESIA - Zulfa Harirah MS; Annas Rizaldi (Syiah Kuala University, 2020)
This paper departs from anxiety about the spread of the Covid 19 virus in Indonesia which is increasing significantly. The government as the main actor in policy making is required to produce policies that are able to reduce and solve covid 19 problems in Indonesia, including the impacts. But the policy will have no meaning if it does not get a response from the recipient of the policy. Therefore this paper is intended to track how the public responds to the reasoning of state policies in dealing with the Covid 19 virus in Indonesia. Through the literature study method, this paper is presented based on the results of readings in journals, books, mass media news to obtain comprehensive results. The rational choice approach to policy making is used as a knife for analysis to sharpen arguments. The results of this paper conclude that the policies taken by the government show rational reasoning. This logical logic of health emergencies can be accepted rationally by the community. However, there was a different response by some people, especially the middle to lower classes. This is caused by social vulnerability caused by limited resources so that it is